Monetary policy strategies for the euro area: Optimal rules in the presence of the ELB - Falk Mazelis; Roberto Motto; Annukka Ristiniemi (European Central Bank (ECB), 2023)
We study alternative monetary policy strategies in the presence of the lower bound on nominal interest rates and a low equilibrium real rate using an estimated DSGE model for the euro area. We demonstrate that simple feedback rules that implement inflation targeting result in a binding lower bound one-fourth of the time as well as inflation and output exhibiting large downward biases and heightened volatility. Rule-based asset purchases that are activated once the policy rate reaches the lower bound are not able to fully offset the destabilizing effects of the lower bound if we assume plausible limits on the size of purchases. Makeup strategies, especially average inflation targeting with a long averaging window, perform better than inflation targeting. However, differences in performance across strategies become small if the response coefficients of the feedback rules are optimized. In addition, we find that the benefits of makeup strategies tend to vanish if agents exhibit a degree of inattention to central bank policies as estimated in the data.
Keywords: E31; E32; E37; E52; E58; E61; E71; 330; Monetary policy; effective lower bound; forward guidance; asset purchases; optimal policy; makeup strategies